Urban management, urban marketing and urban governance: a triptych of sustainable tourism marketing - SAOULI Rim Amina; BENHASSINE Nassira (Journal of North African Economies, 2025)
Today, urban marketing can be a powerful tool for urban management and a fundamental instrument for improving the ability of cities to capitalize on opportunities and maintain their vitality as livable cities. Through the lens of tourism marketing, this article examines the perceptions, attitudes, and actions of marketers and urban managers toward sustainable destinations. In a systematic approach, this article tries to approach the concept of sustainable tourism and to extract the concept of "urban marketing" from the idea of "branding", that of "urban governance" is discovered in the method of "urban management". The study technique applied is largely based on the state of the art, and also on an analytical perspective on examples of inspiring tourism cities.